Rare metal technology 2019 - Azimi, Gisele; Kim, Hojong; Alam, Shafiq; Ouchi, Takanari; Neelameggham, Neal R.; Baba, Alafara Abdullahi (Minerals, metals & materials series., 2019)
This collection presents papers from a symposium on extraction of rare metals as well as rare extraction processing techniques used in metal production. Topics include the extraction and processing of elements such as rare earth metals including yttrium and scandium, gold, vanadium, cesium, zinc, copper, tellurium, bismuth, potassium, aluminum, iridium, titanium, manganese, uranium, rhenium, and tungsten. Rare processing techniques covered include supercritical fluid extraction, direct extraction processes for rare-earth recovery, biosorption of precious metals, and recovery of valuable components of commodity metals such as zinc, nickel, and metals from slag.